Tazza [videorecording (DVD)] : the high rollers - Choi Dong-hoon; Cho, Sŭng-u; Kim, Hye-su, 1970-; Hŏ, Yŏng-man, 1947-; Kim, Se-yŏng, 1973- (5 Points Pictures, 2012)
After discovering he was set up by professional gamblers when he lost his life savings in backroom card game, Goni sets out to learn everything he can about the card game hwatu in order to enter the world of underground gambling and win his money back.